PENGARUH GAYA KEPEMIMPINAN TRASFORMASIONAL REKTOR TERHADAP KINERJA DOSEN DI IKIP PGRI BALI - Citrawan, I Wayan (LP2M IKIP PGRI Bali, 2019)
This research aims to find out whether or not there is the influence of transformational leadership style to the Rector against increased performance lecturer in IKIP PGRI Bali. Data analysis was performed with statistical analysis Based on the level of significance of 5% and N = 102, the magnitude of the numbers zero hypothesis rejection limits of table values Product Moment is = 0.148. When compared to the magnitude of the figures obtained from the results of research that the magnitude of 0.715 rxy, the value obtained from the research results greater than or exceeding zero hypothesis rejection brick figures obtained from table values product moment, so zero hiupotesis asked hoptesis was rejected and accepted which means there is alternatively the influence of transformational leadership style Rector againts performance lecturer. This means the values obtained from rxy research results significantly. Contributions of transformational leadership style Rector on performance lecturer in IKIP PGRI of 51.5%